The Meaning of the Word 'Izzah' in the Qur'an from Toshihiko Izutsu's Semantic Perspective - Sukmaningtyas, Anisa Nur Izzati; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
In an article, it is explained, `Izzah is an attribute of Allah SWT. Only Allah is the true Owner of `Izzah. `Someone can own Izzah according to their approach to Allah; someone close to Him is Rasulullah and Mukminin. On the other hand, there are several phrases of 'Izzah whose meanings are different from the original meaning, namely glory. This study aims to open a broader understanding and knowledge by understanding the meaning of the phrase 'Izzah, ' which is considered odd in its meaning other than glory. This study uses the Qur'anic semantic method developed by Toshihiko Isutzu, with the primary source being the verses of 'Izzah in the Qur'an and the secondary sources in the form of books, dictionaries, journals, theses, articles, and other supporting materials. According to Izutsu, the semantics of the Qur'an are an attempt to reveal the worldview of the Qur'an (Weltanschauung) through semantic analysis of vocabulary or key terms in the Qur'an. The process carried out in this study is to examine the basic meaning and relational meaning of the phrase 'Izzah with syntagmatic and paradigmatic analysis, then examine the phrase in the pre-Qur'anic, Qur'anic, and post-Qur'anic periods. This study concludes that the word 'Izzah has a basic meaning of nobility, self-esteem, strength, and might. From syntagmatic analysis, the meaning of 'Izzah' has five meanings: nobility, arrogance, strength, firmness, and greatness. The diachronic analysis explains three histories: 1) pre-Quranic, the word 'Izzah has the meaning of nobility that is based on something and remains a good trait. 2) In the Qur'anic, the word 'Izzah has eight meanings: protector, arrogance, strength, power, nobility, might, honor, and being tough. 3) post-Qur'anic, the word Izzah means noble and becomes one with Iffah, which means the highest morals that Muslim women must possess.